Edible Insects: A Brief Guide for Polish Consumers - Orkusz, Agnieszka; Orkusz, Martyna (Owady jadalne: Krótki przewodnik dla polskich konsumentów, 2023)
For several years, the concept of consuming insects has been attracting significant interest in Europe, given its potential to provide an environmentally sustainable, meat-alternative source of protein in the diet, not only for animals but also for humans. In Poland at the beginning of 2023, there was a considerable interest around edible insects, but in a negative context. A disinformation campaign was conducted on television and social media, claiming that edible insects threaten human health. It was suggested that consuming insects is a futuristic fad, an ideological madness, a concept conflicting with Polish economic interests, particularly affecting farming areas. This work aimed to present the most important, reliable data regarding edible insects to create a comprehensive and objective informational foundation. This foundation can serve as a basis for making decisions regarding the potential utilisation of insects as a food source.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2023, Nr 39, s. 95-103
Keywords: edible insects; polish consumer; human behaviour; owady jadalne; polski konsument; zachowanie ludzi